THE GAME-BASED CRICKET BOWLING SKILL EXERCISE MODEL FOR CHILDREN AGES 12-15 YEARS - Edenyce Krismartini Eduard; Widiatuti Widiastuti; Johansyah Lubis (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2021)
Abstract. The aim of this study is to produce a game-based cricket bowling skill exercise model by testing the effectiveness of improving bowling skills in children aged 12-15 years. The method used in this study is research and development from Borg and Gall by using 10 stages. The research subjects for group trials and effectiveness are (1) small group trials of 16 children at SD Negeri 15 Pagi Pondok Bambu, (2) large group trials of 25 children at SMP Negeri 2 Kebakkramat, and (3) tests effectiveness of 40 children at Karanganyar Cricket Club.The data collection technique used is the result of expert validation and effectiveness test through an assessment instrument with t-test statistical data analysis. The validity test used by expert justification test, presented 3 experts consisting of: 1 games lecturer, 1 cricket lecturer, and 1 national cricket coach. The final model is produced 15 bowling cricket skill exercise models. The effectiveness test model uses the skills results of cricket bowling. The improvement of bowling cricket skills results showed a significance of t count=14,512, db=39 and p-value=0.00<0.05, which means that there is a significant difference between before and after being given the training model treatment, the pre-test average was 2.23 smaller than the post-test average is 4.47. It can be concluded that the game-based cricket bowling skill training model developed is quite effective for improving bowling skills in children aged 12-15 years.